Nomenclatural notes in the Pleurothallidinae (Orchidaceae): Apoda-prorepentia - Karremans Lok, Adam Philip (2015)
A new species of Acianthera, A. serratifolia, is described and illustrated based on material from Colombia. The species belongs to a small group of species that has alternatively been placed in the genus Apoda-prorepentia. Nevertheless, Apoda-prorepentia is embedded within Acianthera and therefore reduced to synonymy. The required new combinations are proposed.